(untitled) (The Strategic Review for Southern Africa, 2021)
South Africa's cities are focal points in any contemporary snapshot of the country. Their swift transformation within the national landscape means that they now affect or even dominate every other element within it. Its cities and their burgeoning populations have become defining characteristics of the country with their increasing political sway and growing contribution to the national economy. For many people living in cities, their urban affiliation is stronger and more meaningful than an increasingly abstract and distant national affiliation. Cities are important to national branding because they are localised and tangible points where national perception and reputation often originate or are reinforced. For many stakeholders it is city brands that contribute most directly to their perceptions of the national brand in areas such as ease and security of investment, economic status, liveability, tourism, personal interaction or safety and security. This article considers South Africa's largest cities, their competitive positions within the country, in Africa and across the globe, and it does so with a measure of inclusive urbanisation that is relevant to a wide spectrum of South Africa's stakeholders — national and international business and investors, institutions, government and citizens.